2003
DOI: 10.1002/ajmg.b.10069
|View full text |Cite
|
Sign up to set email alerts
|

Association of HFE mutations with neurodegeneration and oxidative stress in Alzheimer's disease and correlation with APOE

Abstract: Oxidative stress enhanced by transition metals such as iron forms an attractive hypothesis for neurodegeneration in Alzheimer's Disease (AD). Iron is increased in the brain in AD, but whether this is a primary abnormality or the result of secondary accumulation is unclear. Among several genetic loci associated with AD, the locus at chromosome 6p21 contains the hereditary hemochromatosis gene HFE. To determine whether a genetic predisposition to iron accumulation is associated with AD, we evaluated three hemoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 36 publications
4
50
1
Order By: Relevance
“…However, it has been shown that hemochromatosis mutations are associated with increased oxidative stress and progression of disease pathology [76] . [78] .…”
Section: Metal Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that hemochromatosis mutations are associated with increased oxidative stress and progression of disease pathology [76] . [78] .…”
Section: Metal Accumulationmentioning
confidence: 99%
“…In addition, Cu + can donate two electrons to oxygen, generating H 2 O 2 [72,73] , and further producing hydroxyl radicals (Fenton-type reaction) [74] . Iron accumulation is also present in cells associated with neuritic plaques in AD [75] , which results in the increase of oxidative stress.However, it has been shown that hemochromatosis mutations are associated with increased oxidative stress and progression of disease pathology [76] . [78] .…”
mentioning
confidence: 99%
“…Iron overload has been postulated to play a role in the pathogenesis of various neurodegenerative diseases such as Parkinson's disease [12], Alzheimer's disease [13,14], and amyotrophic lateral sclerosis [15]. This suggests that the central nervous system is susceptible to iron-induced oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…an endocrinological recruitment to improve the effectiveness of genotyping, and perhaps prevent morbimortality (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%